PENYULUHAN KESEHATAN TENTANG PERUBAHAN FISIK SELAMA KEHAMILAN TRIMESTER III - Hardaniyati; Soekmawaty R.A, Dian; Setyawati, Irni; Herlina, Siskha Maya (Stikes Yarsi Mataram, 2025)
Pregnant women experience physical and psychological changes that can cause discomfort. Physical changes experienced by pregnant women include changes in blood volume, abdominal enlargement, breast enlargement, skin changes to become darker, changes in the respiratory tract so that the mother feels short of breath, hormonal changes and the digestive tract that cause nausea and vomiting and constipation. Efforts that can be made are to provide health education on preventing or treating back pain in pregnant women, one of which is pregnancy gymnastics, including transverse exercises, pelvic floor exercises, and general stretching. The purpose of this community service activity is to provide an understanding to pregnant women about the changes that occur, so that pregnant women do not experience unexpected problems. This community service activity was carried out at the Labuapi Health Center, which was attended by 26 people. The results of this community service were an increase in mothers' knowledge about physical changes by 90%, thereby reducing the occurrence of unexpected problems. Conclusion With knowledge about physical changes, pregnant women can take steps to control or minimize their negative impacts. Counseling can help pregnant women overcome physical discomfort that often occurs, such as back pain or leg cramps, by using various relaxation techniques or pregnancy gymnastics. By understanding the various physical changes, pregnant women can prepare themselves mentally and physically for the labor process, including knowing the signs of labor and how to deal with pain during labor.